The quality of life (QoL) of advanced stage lung adenocarcinoma patients receiving afatinib at Dr. Sardjito General Hospital, Yogyakarta - Bayu Prio Septiantoro; Retno Murwanti; Dyah Aryani Perwitasari; Mustofa (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2025)
Lung cancer has the highest mortality rate of all cancers. In its advanced stages, this disease is associated with poor survival rates and quality of life. The most common subtype of lung cancer is adenocarcinoma which is frequently associated with mutations in the epidermal growth factor receptor (EGFR), a protein crucialfor cell proliferation. The presence of EGFR mutations plays a key role in targeted therapy using tyrosine kinase inhibitors (TKIs). Afatinib is a second-generation TKI that offers several advantages over the first-generation. Afatinib is effective against complex and uncommon EGFR mutations, making it a commonly usedoption for patients with lung adenocarcinoma. However, afatinib is also associated with a higher incidence of adverse drug reactions (ADRs) compared to other TKIs, which may impact therapeutic outcomes. This study aimed to assess the quality of life (QoL) of advanced lung adenocarcinoma patients with EGFR mutations andthe prevalence of ADRs associated with afatinib treatment at Dr. Sardjito General Hospital in Yogyakarta. The study employed an observational cross-sectional design. Prospective data collection was conducted for two months, from January to February 2025 at the Oncology Department following ethical approval. A totalof 15 patients were enrolled in this study. The most commonly identified ADRs were acne (45%), diarrhea (20%), paronychia (20%), and oral mucositis (15%). The mean QoL scores was 81.38 ± 10.01 for the functional scale, 15.93 ± 8.48 for the symptom scale, and 72.78 ± 19.53 for global health status.